A existência de vigilância por parte dos empregadores restringe a liberdade dos utilizadores nas redes sociais - Casanova, Susana Salazar (2019)
Artigo baseado na comunicação proferida no 1st International Meeting of Industrial Sociology, Sociology of Organizations, and work: “ Work, social change and economic dynamics: Challenges for contemporary societies”. Escola Superior de Educação do Instituto Politécnico de Lisboa, 27-28 novembro 2014